Nothofagus trees show genotype difference that influence infection by mistletoes, Misodendraceae - Vidal Russell, Romina; Premoli Il'grande, Andrea Cecilia (Australian Journal of Botany)
Nothofagus trees host Misodendrum, an endemic mistletoe of the subantarctic forests of Chile and Argentina. Differences in the infection intensity on a given host and patches of infected trees are observed within the forest. We used allozymes to test for genetic differences between uninfected and infected Nothofagus trees (Nothofagus antarctica (G. Forst.) Oerst.) by two species of Misodendrum (Misodendrum linearifolium DC. and Misodendrum punctulatum DC.) at three sites. Non-metric multidimensional scaling ordination was performed using the presence of each of 26 total alleles in 166 trees of N. antarctica (89 uninfected and 77 infected). Sites with higher degrees of infection by M. punctulatum can be distinguished in the ordination. The number of infections per tree has a significant correlation with the ordination axis. ANOSIM analysis showed significant differences between infected and uninfected trees when they were infected by M. punctulatum but not by M. linearifolium. Differences between sites were also found, but the two sites with higher degrees of infection by M. punctulatum did not differ from each other. The intrapopulation genetic structure of N. antarctica could be maintained by the mistletoe Misodendrum through host selection. Fil: Vidal Russell, Romina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Patagonia Norte. Instituto de Investigación en Biodiversidad y Medioambiente; Argentina. Universidad Nacional del Comahue. Centro Regional Universitario Bariloche. Laboratorio de Ecotono; Argentina Fil: Premoli Il'grande, Andrea Cecilia. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Patagonia Norte. Instituto de Investigación En Biodiversidad y Medioambiente; Argentina. Universidad Nacional del Comahue. Centro Regional Universitario Bariloche. Laboratorio de Ecotono; Argentina